CAN YOU T.E.A.C.H. ADOLESCENTS? - Kamberk-Kilicci , M. (Modern Psychology, 2019)
The main question underlying this study refers to how teachers may be helped to address the psychological factors associated with the well-being of their adolescent students. In the realm of professional development, the teachers are offered to review their background knowledge about the psychology of adolescents and use what research and experience have taught to support, encourage and enhance their students’ learning. The adolescent is obviously central to the equation with his/her typical characteristics of increased detachment from adults, overall emotional vulnerability, the emphasis on the peer group and the essential search for identity. The second refrain has to do with the various roles of the teacher as a person, what he/she needs to know and how he/she needs to be in order to provide his/her students with the opportunities to learn in ways that meet their various needs. Finally, the third and last chapter elaborates on what T.E.A.C.H. means: T for thought; E for empathy; A for activity; C for choice and H for harmony. It also provides a discussion about how each aspect evolves with time and integrates within the scope of research relative to the domain of teaching and psychology.